Talking about Practices: On Julian Orr’s Talking About Machines - Yanow, Dvora (Organization studies, 2006)
Julian Orr’s ethnographic study of copier technicians explores three themes—practices, practitioners, and learning—gathered under the heading of ‘work’ and situated in geographic spaces—the team’s territory—and places. In my reading, the book addresses three central concerns in organizational studies today: moves to (re-)ground theorizing in work practices, drawing on methods suitable for studying what it is that people in organizations actually do; developing practice-based understandings of organizational learning; and attending to the settings—the places and spaces—in which those practices take place.